Pengaruh Model Teaching Games For Understanding (TGFU): Terhadap Pemahaman Bermain - Resti Puspita Ardiani; Lukmannul Haqim Lubay; Achmad Syakur Fahri (Jurnal Porkes, 2026)
This study was motivated by students’ limited understanding of the basic concepts of futsal, such as passing, kicking, positioning, teamwork, and sportsmanship. This situation highlights the need to implement a more appropriate and effective learning model in physical education. This study aims to determine the effect and level of effectiveness of the Teaching Games for Understanding (TGfU) learning model on students’ understanding of futsal. The research method used was quantitative with a one-group pretest-posttest design. The sample consisted of 17 third- and fourth-grade students in the futsal extracurricular program, selected using purposive sampling. The instrument used was the GPAI (Game Performance Assessment Instrument), which measures seven components of game understanding, while data analysis included the Shapiro-Wilk normality test, Levene’s homogeneity test, paired-sample t-test, N-Gain Score, and Cohen’s d effect size. The results showed an increase in the average score from 15.18 on the pretest to 24.71 on the posttest, a difference of 9.53 points. The paired-sample t-test yielded a p-value of 0.000 (< 0.05), an average N-Gain Score of 0.58 (moderate category), and a Cohen’s d effect size of 2.37 (large category). The conclusion of this study is that the TGfU learning model has a significant effect and is highly effective in improving students’ understanding of futsal gameplay.